Regioselective and efficient enzymatic synthesis of antimicrobial andrographolide derivatives - Patil, Harshal S.; Jadhav, Dipesh D.; Paul, Ajay; Mulani, Fayaj A.; Karegaonkar, Shrikant J.; Thulasiram, Hirekodathakallu V. (Bioorganic & Medicinal Chemistry Letters, 2018)
Labdane diterpene andrographolide (1) is a major constituent of Andrographis paniculata and known to exhibit wide spectrum of biological activities. In this study, regioselective monoesters of (1) have been synthesized by using Amano lipase AK (Pseudomonas fluorescens) as a biocatalyst. Amano lipase AK was able to execute highly efficient esterification of hydroxyl group attached to C-14 carbon of (1) in presence of acyl donors. Among the various synthesized derivatives including two novel compounds such as andrographolide-14-propionate (3) and andrographolide-14-caproate (5) displayed antimicrobial activity against Staphylococcus aureus with low minimal inhibitory concentration (MIC) 4 mu g/mL and 16 mu g/mL respectively. Furthermore, they have shown low hemolysis activity at their respective MIC and increase in the permeability of the bacterial cell membrane as delineated by FITC uptake and SEM imaging studies. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Acylation; Andrographolide; Antimicrobial activity; biocatalysis; Hemolysis; Lipase; Natural product

Biological synthesis of alpha-Ag2S composite nanoparticles using the fungus Humicola sp. and its biomedical applications - Syed, Asad; Saedi, Marzouq Hussain Al; Bahkali, Ali H.; Elgorban, Abdallah M.; Kharat, Maheshkumar; Pai, Kalpana; Ghodake, Gajanan; Ahmad, Absar (Journal of Drug Delivery Science and Technology, 2021)
Synthesis of alpha-Ag2S (silver sulfide) is a highly challenging task, usually attempted using synthetic, hazardous chemical processes. This report puts efforts to exploring microbial-based eco-friendly alternatives. A facile, onepot biological method for the synthesis of alpha-Ag2S composite nanoparticles (NPs) in an aqueous medium at ambient conditions was established. As prepared alpha-Ag2S composite NPs were efficiently produced from precursors silver nitrate and sodium sulfite. The extracellular biomolecules produced by Humicola sp. reduced the precursor solution and at the same time it capped the formed Ag2S NPs. The characterization performed by different techniques revealed excellent optical, morphological, and structural properties (size, shape distribution, and crystallinity) of the alpha-Ag2S NPs. The change in color from colorless to dark brown indicated the formation of alpha-Ag2S, which was further confirmed by fluorescence and UV-Visible spectroscopy, showing a sharp peak at 410 nm. Morphological analysis of alpha-Ag2S NPs confirmed the spherical shape, and narrow size distribution. alpha-Ag2S NPs were found to be potent in antimicrobial applications owing to their high dispersibility in water and capping by extracellular biomolecules secreted by Humicola sp. The anti-cancer activity for alpha-Ag2S performed using human breast cancer cell line (ZR-75-1) and human Burkitt's lymphoma cancer (Daudi). The biocompatibility test was performed using human peripheral blood mononuclear cells (PBMCs) for alpha-Ag2S NPs. The anti-leishmania activity was also determined for alpha Ag2S NPs in-vitro using the standard anti-promastigote protocol (Leishmania donovani promastigotes). This extracellular system is an economically and environmentally benign route for the biosynthesis of alpha-Ag2S NPs having desired surface, structure and biomedical properties.
Keywords: Cytotoxicity; Fungus; Hemolysis; Humicolasp; Silver sulfide(alpha-Ag2S)

Alpha Au2S nanoparticles: fungal-mediated synthesis, structural characterization and bioassay - Syed, Asad; Al Saedi, Marzouq H.; Bahkali, Ali H.; Elgorgan, Abdallah M.; Kharat, Mahesh; Pai, Kalpana; Pichtel, John; Ahmad, Absar (Green Chemistry Letters and Reviews, 2022)
Luminescent nanoparticles synthesized via bio-based protocols that generate nanoparticles having different chemical compositions along with other functionalities (size and morphology) have received huge attention. We have focused our research on gold sulfide nanoparticles (Au2S NPs) and have biosynthesized these NPs using the fungus Humicola sp. The nanoparticles were characterized by Transmission Electron Microscopy, which showed spherical morphology of Au2S. UV-Visible-NIR spectrophotometry, luminescence spectrophotometry, Selected Area Electron Diffraction, Energy Dispersive Analysis of X-rays, and X-ray diffraction were performed. FTIR confirmed that the fungal metabolites including biomolecules secreted in the reaction medium are primarily responsible for nanoparticle synthesis and stabilization. The fungus reduced the precursor solution (HAuCl4 and Na2SO3) and at the same time capped them with secreted biomolecules. The anti-leishmanial activity of Au2S NPs was determined against L. donovani promastigote (Ag83 strain). Au2S NPs displayed less cytotoxicity towards both normal and cancer (Daudi, ZR-75-1) cell lines. Hemocompatibility was determined via hemolysis assays. This novel fungal-based system demonstrates an economical and environmentally benign process for biosynthesis of Au2S nanoparticles which may find application in bioimaging and labeling studies.
Keywords: Biosynthesis; Cytotoxicity; Gold sulfide; Hemolysis; humicola sp; promastigote